Socialization of The Use of The JKN Mobile Application in Health History Screening at Loa Janan Health Center - Yulianti Yulianti; Purwo Setiyo Nugroho; Ainur Rachman; Ade Dwi Karmila; Cindy Oktavia Ananta; Della Fitria Zachrailly; Desi Puspitasari; Indah Widyawati Sari; Jubaidah Jubaidah; Kasih Nadhirah; Nadia Tajudin (ABDIMAYUDA: Indonesia Journal of Community Empowerment for Health, 2023)
The application of Information and Communication Technology is widely used in the world of work, one of which is in the health sector, there is the Mobile JKN application, the lack of public knowledge, especially the elderly, is experiencing problems, whether they do not have a smartphone or do not understand how to use the Mobile JKN application. The purpose of this activity is to add to the public's insight and knowledge about how to use and benefit the Mobile JKN application in health history screening. The method used is direct socialization and discussion using poster media to assist in the delivery of socialization so that it is easily understood by the community. The target for this activity were patients who visited the Loa Janan Health Center. This socialization activity was enthusiastically attended by participants who were able to receive information well and were active in conducting discussions at the end of the participant's activities as well as supporting application optimization. The results of the health screening socialization activity showed an increase in patient knowledge, namely 90% and participants' understanding, especially the elderly, of using the Mobile JKN application. The conclusion from the socialization activities carried out is very effective in solving existing problems and increasing public understanding of information, and how to use Mobile JKN in health screening.